Broadband low-frequency sound absorption by periodic metamaterial resonators embedded in a porous layer. (24th November 2019) - Zhu, Xing-Feng; Lau, Siu-Kit; Lu, Zhenbo; Jeon, Wonju
Abstract: Broadband absorption of the audible sound wave at low frequency has been achieved by using periodic acoustic metamaterial resonators (AMRs) embedded inside a porous layer. A single AMR embedded in a porous layer could reach perfect absorption (PA) at the resonance frequency, and it can be easily tuned by adjusting the inner radius of AMR. With four AMRs in the porous layer, a high absorption (>80%) is obtained in the frequency range from 180 Hz to 550 Hz, while the thickness of the porous layer is only 1 / 10 of the relevant wavelength at 300 Hz. The broadband and high absorption performances are due to the interferences of the low-frequency resonances of the AMRs and the energy trapping between the AMRs and the rigid backings. The finite element simulations are experimentally validated. Moreover, the broadband low-frequency absorption is robust under various oblique incidence even at large incident angles. The effects of the acoustic parameters of the porous layer on the absorption properties are also discussed. The absorbers should have high potential for the practical applications in buildings, aircrafts and automobiles due to their ease of fabrication, ultra-thin, and robust high-efficiency.